2016
DOI: 10.1017/s1368980016000379
|View full text |Cite
|
Sign up to set email alerts
|

Eating breakfast together as a family: mealtime experiences and associations with dietary intake among adolescents in rural Minnesota, USA

Abstract: Objective Although existing evidence links breakfast frequency to better dietary quality, little is known specifically in regards to the benefits associated with eating breakfast together with one's family. This study describes the prevalence and experience of having family meals at breakfast among rural families and examines associations between meal frequency and adolescent diet quality. Design Data were drawn from Project BreakFAST, a group-randomized trial aimed at increasing school breakfast participati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 47 publications
0
39
0
Order By: Relevance
“…children with cystic fibrosis or diabetes) and (iii) the study reported insufficient statistics to calculate an effect size. Using these criteria, we arrived at a total of 57 studies .…”
Section: Methodsmentioning
confidence: 99%
“…children with cystic fibrosis or diabetes) and (iii) the study reported insufficient statistics to calculate an effect size. Using these criteria, we arrived at a total of 57 studies .…”
Section: Methodsmentioning
confidence: 99%
“…Eligible children were between the 50 th and 95 th percentile for age and sex-adjusted height and weight—as measured by the CDC standardized growth charts. 24,25 Additionally, potential participants were eligible for GROW if they received at least one form of government assistance, spoke English or Spanish, the parent was over 18 years old, and both parent and child could participate in physical activity. The GROW intervention is a staged-intensity behavioral intervention.…”
Section: Methodsmentioning
confidence: 99%
“…14,21,22 While research suggests that family meals are protective for child diet quality and potentially weight status, little research has examined whether it matters if the family meal is breakfast, lunch, or dinner. 23,24 It is important to understand whether one meal type conveys more positive impact on child diet quality and weight status than another to inform research regarding which meals should be targeted in nutrition interventions. For example, if families are more likely to serve vegetables and fruits at dinner then it may be important for interventions to target serving vegetables and fruits at family breakfast meals and/or lunches.…”
Section: Introductionmentioning
confidence: 99%
“…There is an extensive literature on the social and environmental factors that impact adolescents' decision making around diet and activity. [2][3][4][5][6][7][8][9] In particular, the school environment has been well studied, both as a formative environment shaping diet and activity behaviors and, consequently, a potential site for interventions a These authors contributed equally. designed to promote healthy behaviors.…”
Section: Introductionmentioning
confidence: 99%